Optimization of H2O2 Production in Biological Systems for Design of Bio-Fenton Reactors - Peiguo Zhou; Liping Yang; Wenjing Yang; Jiaxin Hou; Ziqiao Liao (Microorganisms, 2024)
The treatment of antibiotic wastewater, which is known for its micro-toxicity, inhibition, and poor biochemistry, poses significant challenges, including complex processes, high energy demands, and secondary pollution. Bio-Fenton, a novel Fenton technology, enables the in situ production of H2O2 at near-neutral pH, having low energy requirements and sustainable properties, and reduces the hazards of H2O2 transportation and storage. We preliminary self-designed a heterogeneous Bio-Fenton reactor. An aerobic SBBR system with pure algae, pure bacteria, and bacteria–algae symbiosis was first constructed to investigate the optimal process conditions through the effects of carbon source concentration, light duration, bamboo charcoal filling rate, and dissolved oxygen (DO) content on the H2O2 production and COD removal. Second, the reactor was constructed by adding iron-carrying catalysts to remove ROX and SDZ wastewater. The results demonstrated that the optimal operating parameters of aerobic SBBR were an influent carbon source concentration of 500 mg/L, a water temperature of 20 ± 2 °C, pH = 7.5, a dissolved oxygen content of 5 mg/L, a light–dark ratio of 12 h:12 h, a light intensity of 2500 Lux, an HRT of 10 h, and a bamboo charcoal filling rate of 33%. Given these conditions, the bacterial–algal system was comprehensively found to be the most suitable biosystem for this experiment. Ultimately, the dynamically coupled Bio-Fenton process succeeded in the preliminary removal of 41.32% and 42.22% of the ROX and SDZ from wastewater, respectively.